Preparation method of high-density solid electrolyte and lithium battery
Through the two-stage heat treatment method, the problems of high sintering temperature and long insulation time during the preparation of oxide electrolyte are solved, and the preparation of high-density solid electrolyte is realized, which reduces energy consumption and improves the conductivity.
Patent Information
- Application Number
- CN202510153143.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation of oxide electrolyte, the sintering temperature is high and the insulation time is long, resulting in large energy consumption.
The two-stage heat treatment method is adopted, the heating temperature of the first stage is 900~1300℃, the insulation is 0~30 minutes, and the second stage is cooled by at least 60℃ and then the insulation is 2~30 hours. This method is used to prepare high-density solid electrolyte.
It reduces the energy consumption of the sintering process, shortens the high-temperature insulation time, and improves the density of the electrolyte and lithium ion conductivity.
Smart Images

Figure CN119627201A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to lithium battery electrolytes, and in particular to solid electrolytes. Background Art
[0002] Conventional lithium batteries use organic solvents as electrolytes, which pose safety risks such as liquid leakage, fire and explosion. If they are replaced with solid electrolytes, the safety issues of flammability and explosion can be solved. At the same time, the energy density of the battery can be greatly improved by being compatible with lithium metal negative electrodes. The research and development routes for solid electrolytes are mainly concentrated on oxide electrolytes, sulfide electrolytes, chloride electrolytes and polymer electrolytes. Among them, oxide electrolytes have both conductivity and stability, and the difficulty of mass production is moderate. At present, the development progress is relatively fast.
[0003] One of the main problems facing oxide electrolytes today is how to further improve lithium ion conductivity. Studies have shown that the bulk ionic conductivity of oxide electrolyte sheets is often several orders of magnitude higher than the grain boundary ionic conductivity. Therefore, increasing the density of the electrolyte sheet and increasing the grain boundary ionic conductivity are the keys to improving the overall ionic conductivity. Currently, the most widely used sintering method is powder burying sintering. The formed electrolyte green body is heated to a suitable temperature and kept warm for a period of time. The green body undergoes sintering shrinkage to complete densification. This method is easy to operate, but in order to achieve a higher density, a higher sintering temperature, a longer insulation time, and a higher energy consumption are required. Summary of the invention
[0004] The embodiments of the present application provide a method for preparing a high-density solid electrolyte and a lithium battery to solve the technical problems of high sintering temperature and long insulation time in the preparation process of oxide electrolyte.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a high-density solid electrolyte, the method for preparing a high-density solid electrolyte comprising the following steps: Providing oxide electrolyte powder; pressing the oxide electrolyte powder into a green compact; The green body is heated to 900-1300° C. and kept at this temperature for 0-30 minutes; The green body is cooled by at least 60° C. and then kept warm for 2 to 30 hours to obtain the high-density solid electrolyte.
[0006] In some embodiments of the present application, the green body is cooled by at least 60° C., and the temperature of the green body after cooling is 700-1150° C.
[0007] In some embodiments of the present application, the particle size distribution of the oxide electrolyte powder satisfies the following conditions: 50nm≤D50≤5μm.
[0008] In some embodiments of the present application, the green body is heated to 900-1300° C., and the heating rate is 2-10° C. / min; and / or, The green body is cooled by at least 60° C., and the cooling rate is not less than 5° C. / min.
[0009] In some embodiments of the present application, the surface of the green body is completely covered with powder of the same material as the green body during the sintering process.
[0010] In some embodiments of the present application, the material of the oxide electrolyte powder is pure lithium lanthanum zirconium oxide or pure lithium titanium aluminum phosphate.
[0011] In some embodiments of the present application, the material of the oxide electrolyte powder is lithium lanthanum zirconium oxide doped with a first doping element and maintaining a garnet structure, and the first doping element is at least one of B, Al, Ga, Zn, Fe, Be, Na, K, Rb, Ca, Sr, Ba, Ti, Mn, Co, Nb, Mo, Tc, Ru, Pd, Hf, Ta, and W.
[0012] In some embodiments of the present application, in the oxide electrolyte powder, the molar ratio of lithium atoms to the first doping element atoms is not less than 7:4.
[0013] In some embodiments of the present application, the material of the oxide electrolyte powder is lithium aluminum titanium phosphate doped with a second doping element, and the second doping element is doped by replacing Al or Ti in the lithium aluminum titanium phosphate, and the second doping element is at least one of Sc, Fe, Cr, In, Ge, Zr, Sn, Hf, etc.
[0014] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a high-density solid electrolyte prepared by the method described in any embodiment of the first aspect.
[0015] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art: The preparation method of the high-density solid electrolyte provided in the embodiment of the present application is to treat the green body by a two-stage heat treatment, and the heat treatment temperature of the first stage is 900~~1300℃. The temperature at this stage is relatively high, and the main changes in the green body are the rapid migration of grain boundaries and the growth of grain size. After the second stage is reduced by at least 60℃, the temperature is reduced, and the grain size no longer grows rapidly. The main changes in the green body are inter-grain diffusion and mass transfer, exhausting pores and completing densification. The method described in this application can prepare a high-density solid electrolyte, and the insulation time of this application at 900~~1300℃ is short, and the longest insulation stage is lower than the traditional electrolyte sintering method in temperature, and energy consumption is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0018] Figure 1 A schematic flow chart of a method for preparing a high-density solid electrolyte provided in an embodiment of the present application. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0021] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0022] The existing oxide electrolyte preparation process has technical problems such as high sintering temperature and long insulation time.
[0023] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows: In a first aspect, an embodiment of the present application provides a method for preparing a high-density solid electrolyte, the method for preparing a high-density solid electrolyte comprising the following steps: S1: providing oxide electrolyte powder; S2: pressing the oxide electrolyte powder into a green compact; S3: heating the green body to 900-1300° C. and keeping the temperature for 0-30 min; S4: Cooling the green body by at least 60° C. and then keeping the temperature for 2 to 30 hours to obtain the high-density solid electrolyte.
[0024] The oxide electrolyte powder described in the present application can be prepared by solid phase synthesis after ball milling, sol-gel method, hydrothermal method and the like.
[0025] As an example, the green body in step S3 may be heated to 900°C, 1000°C, 1100°C, 1200°C, or 1300°C.
[0026] Existing oxide electrolyte sintering is usually carried out at 900~1300℃ until the electrolyte is sintered.
[0027] The present application uses a two-stage heat treatment for the green body, and the heat treatment temperature of the first stage is 900~~1300℃. The temperature at this stage is relatively high, and the main changes in the green body are rapid migration of grain boundaries and growth of grain size. After the second stage is reduced by at least 60℃, the temperature is reduced, and the grain size no longer grows rapidly. The main changes in the green body are diffusion and mass transfer between grains, discharge of pores and completion of densification. The method described in this application can prepare a high-density solid electrolyte, and the insulation time of this application at 900~~1300℃ is short, and the longest insulation stage is lower in temperature and energy consumption compared to the traditional electrolyte sintering method.
[0028] In some embodiments of the present application, the green body is cooled by at least 60° C., and the temperature of the green body after cooling is 700-1150° C.
[0029] It is easy to understand that the beneficial effect of the green body having a temperature of 700-1150° C. after cooling is that it can fully diffuse and transfer mass between grains in the green body, discharge pores and complete densification.
[0030] As an example, the temperature of the green body after cooling can be 700°C, 800°C, 900°C, 1000°C, 1100°C, or 1150°C.
[0031] In some embodiments of the present application, the particle size distribution of the oxide electrolyte powder satisfies the following conditions: 50nm≤D50≤5μm.
[0032] The beneficial effect of the particle size distribution of the oxide electrolyte powder satisfying the above conditions is that the size of the grains in the green body is made more uniform, the diffusion and mass transfer between the grains in the green body is made more sufficient, and the densification is made more sufficient.
[0033] In some embodiments of the present application, the green body is heated to 900-1300° C., and the heating rate is 2-10° C. / min; and / or, The green body is cooled by at least 60° C., and the cooling rate is not less than 5° C. / min.
[0034] It is easy to understand that the beneficial effect of the heating rate of 2-10°C / min is that the green body is heated faster and the grain growth process is also relatively stable and uniform.
[0035] As an example, the heating temperature rise rate may be 2°C / min, 4°C / min, 6°C / min, 8°C / min, or 10°C / min.
[0036] It is easy to understand that the beneficial effect of the cooling rate of not less than 5°C / min is to cool the green body as quickly as possible while ensuring that the temperature of the green body changes evenly and smoothly, so as to inhibit the further rapid growth of the grain size and make the diffusion mass transfer between the grains the main change in the green body.
[0037] In some embodiments of the present application, the surface of the green body is completely covered with powder of the same material as the green body during the sintering process.
[0038] It is easy to understand that covering the surface of the green body with powder of the same material can reduce the volatilization of the Li element without affecting the elemental composition of the green body.
[0039] In some embodiments of the present application, the material of the oxide electrolyte powder is pure lithium lanthanum zirconium oxide or pure lithium titanium aluminum phosphate.
[0040] It is easy to understand that the chemical formula of pure lithium lanthanum zirconium oxygen is Li7La3Zr2O 12 The chemical formula of pure lithium aluminum titanium phosphate is Li 1+ x Al x Ti 2−x (PO4)3, where 0<x<2.
[0041] In some embodiments of the present application, the material of the oxide electrolyte powder is lithium lanthanum zirconium oxide doped with a first doping element and maintaining a garnet structure, and the first doping element is at least one of B, Al, Ga, Zn, Fe, Be, Na, K, Rb, Ca, Sr, Ba, Ti, Mn, Co, Nb, Mo, Tc, Ru, Pd, Hf, Ta, and W.
[0042] It is easy to understand that lithium lanthanum zirconium oxide with a garnet structure has good performance as an electrolyte; the present application can be applied to pure lithium lanthanum zirconium oxide and lithium lanthanum zirconium oxide that still maintains a garnet structure after doping treatment.
[0043] In some embodiments of the present application, in the oxide electrolyte powder, the molar ratio of lithium atoms to the first doping element atoms is not less than 7:4.
[0044] In some embodiments of the present application, the material of the oxide electrolyte powder is lithium aluminum titanium phosphate doped with a second doping element, and the second doping element is doped by replacing Al or Ti in the lithium aluminum titanium phosphate, and the second doping element is at least one of Sc, Fe, Cr, In, Ge, Zr, Sn, Hf, etc.
[0045] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a high-density solid electrolyte prepared by the method described in any embodiment of the first aspect.
[0046] The lithium battery is implemented based on the method described in any embodiment of the first aspect. The specific implementation of the lithium battery can refer to the above embodiments and common knowledge in the field. Since the lithium battery adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0047] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0048] Example 1 This embodiment provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: Raise the temperature in the muffle furnace to 1280°C at a heating rate of 10°C / min and keep it at that temperature for 1 min; Sd: The temperature in the muffle furnace was cooled to 1120° C. at a rate of 7° C. / min and kept at this temperature for 12 h to obtain the high-density solid electrolyte.
[0049] Example 2 The only difference between this embodiment and embodiment 1 is that the insulation temperature in step Sc is 1250° C. and the insulation time is 3 minutes, and the insulation temperature in step Sd is 1150° C.
[0050] The details are as follows: This embodiment provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: Raise the temperature in the muffle furnace to 1250°C at a heating rate of 10°C / min and keep it at that temperature for 3 min; Sd: The temperature in the muffle furnace was cooled to 1150° C. at a rate of 7° C. / min and kept at this temperature for 12 h to obtain the high-density solid electrolyte.
[0051] Example 3 The only difference between this embodiment and embodiment 1 is that the insulation temperature in step Sc is 1220° C. and the insulation time is 10 min, and the insulation temperature in step Sd is 1160° C.
[0052] The details are as follows: This embodiment provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: Raise the temperature in the muffle furnace to 1220°C at a heating rate of 10°C / min and keep it at that temperature for 10 min; Sd: The temperature in the muffle furnace was cooled to 1160° C. at a rate of 7° C. / min and kept at this temperature for 12 h to obtain the high-density solid electrolyte.
[0053] Comparative Example 1 The difference between this comparative example and Example 3 is that step Sd is not implemented and the holding time in step Sc is 12 h.
[0054] The details are as follows: This comparative example provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: The temperature in the muffle furnace is raised to 1220° C. at a heating rate of 10° C. / min and kept at this temperature for 12 min to obtain the high-density solid electrolyte.
[0055] Comparative Example 2 The only difference between this comparative example and Example 3 is that step Sd is not implemented, and the holding temperature in step Sc is 1200° C. and the holding time is 12 h.
[0056] The details are as follows: This comparative example provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: The temperature in the muffle furnace is raised to 1200° C. at a heating rate of 10° C. / min and kept at this temperature for 12 min to obtain the high-density solid electrolyte.
[0057] Comparative Example 3 The only difference between this comparative example and Example 3 is that step Sd is not implemented, and the holding temperature in step Sc is 1180° C. and the holding time is 12 h.
[0058] The details are as follows: This comparative example provides a method for preparing a high-density solid electrolyte, which is implemented by the following steps: Sa: Take 0.5g Li 6.55 Ga 0.15 La3Zr2O 12 The powder was added into a tableting mold with a diameter of 10 mm, and then slowly pressurized to 350 MPa and maintained for 5 min to obtain a green body; Sb: Place the green body in a corundum crucible and completely cover it with electrolyte powder of the same composition, then place the corundum crucible into a muffle furnace; Sc: The temperature in the muffle furnace is raised to 1180° C. at a heating rate of 10° C. / min and kept at this temperature for 12 min to obtain the high-density solid electrolyte.
[0059] Related experiments and effect data: The density, lithium ion conductivity and lithium content of the high-density solid electrolytes obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested according to the industry standard T / SPSTS 019-2021. The specific results are shown in Table 1.
[0060] Table 1 Test results of high-density solid electrolyte It can be found from Table 1 that compared with the two-stage heating of Examples 1 to 3, the high-density solid electrolyte obtained by the one-stage heating of Comparative Examples 1 to 3 has a lower density overall, and the lithium ion conductivity decreases accordingly, which shows that the two-stage heating of Examples 1 to 3 is beneficial to increasing the density of the solid electrolyte; the Li content increases as the temperature of the main insulation stage decreases, and has little correlation with the density.
[0061] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0062] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of the three associated objects can exist alone, or any at least two of them can exist at the same time. For example, for A, and / or B, and / or C, it can mean that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" means one or more, and "multiple" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0063] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a high-density solid electrolyte, characterized in that: The preparation method of the high-density solid electrolyte comprises the following steps: Providing oxide electrolyte powder; pressing the oxide electrolyte powder into a green compact; The green body is heated to 900-1300° C. and kept at this temperature for 0-30 minutes; The green body is cooled by at least 60° C. and then kept warm for 2 to 30 hours to obtain the high-density solid electrolyte.
2. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The green body is cooled by at least 60° C., and the temperature of the green body after cooling is 700-1150° C.
3. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The particle size distribution of the oxide electrolyte powder satisfies the following conditions: 50nm≤D50≤5μm.
4. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The green body is heated to 900-1300° C., and the heating rate is 2-10° C. / min; and / or, The green body is cooled by at least 60° C., and the cooling rate is not less than 5° C. / min.
5. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: During the sintering process, the surface of the green body is completely covered with powder of the same material as the green body.
6. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The material of the oxide electrolyte powder is pure lithium lanthanum zirconium oxide or pure lithium aluminum titanium phosphate.
7. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The material of the oxide electrolyte powder is lithium lanthanum zirconium oxide doped with a first doping element and maintaining a garnet structure, wherein the first doping element is at least one of B, Al, Ga, Zn, Fe, Be, Na, K, Rb, Ca, Sr, Ba, Ti, Mn, Co, Nb, Mo, Tc, Ru, Pd, Hf, Ta, and W.
8. The method for preparing a high-density solid electrolyte according to claim 7, characterized in that: In the oxide electrolyte powder, the molar ratio of lithium atoms to the first doping element atoms is not less than 7:
4.
9. The method for preparing a high-density solid electrolyte according to claim 1, characterized in that: The material of the oxide electrolyte powder is lithium aluminum titanium phosphate doped with a second doping element, wherein the second doping element is doped by replacing Al or Ti in the lithium aluminum titanium phosphate, and the second doping element is at least one of Sc, Fe, Cr, In, Ge, Zr, Sn, and Hf.
10. A lithium battery, characterized in that: The lithium battery comprises a high-density solid electrolyte prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Compact submicron-grain beta''-Al2O3 product, preparation method and application thereof
CN107365151A
Sintering method for preparing dense garnet-type lithium ion solid electrolyte
CN109037759A
Positive electrode material, preparation method thereof and lithium ion battery
CN109796052A
NASICON type lithium ion solid electrolyte, preparation method and battery
CN113346127A
Cited By
Gel injection molding method for ceramic electrolyte of solid sodium salt battery for energy storage
CN121872758A